The impact of renewable energy, green economy, and blue economy on economic growth - Suci, Stannia Cahaya; Siahaan, Olindayanti; Herlina, Deswita (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
Over the last 20 years, the general trend of economic growth in the European Union shows a slow growth rate, especially in continental economies. Various factors affect the sluggish economic growth in the European Union. This study aims to partially and simultaneously determine the effect of Euribor interest rates, exchange rates, renewable energy consumption, green bond issuance, and production on economic growth in 14 European Union countries for 2014-2022. Estimation is done using the generalized method of moments (GMM) analysis. The estimation results show that the Euribor interest rate and aquaculture production significantly positively affect economic growth. In contrast, the lag-dependent variable of economic growth and renewable energy consumption significantly negatively impacts economic growth. Meanwhile, exchange rates and green bond issuance are not significant to economic growth in 14 EU countries. Therefore, policies that support the stability of interest and exchange rates, increase the effectiveness of green investment, and optimize fiscal incentives and funding for strategic sectors, including renewable energy and aquaculture, are needed to accelerate economic growth in the European Union.